Gender and Ethnic/Racial Differences in Community College Student Enrollmentin Honors Courses: A National Study (Global Journal of Human-Social Science, 2017)
Examined in this study was the gender and ethnic racial composition of students who had participated in community college honors courses Data were gathered from the Community College Survey of Student Engagement a 38 question instrument in which information was obtained about student perceptions of the academic and nonacademic community college environment The data that were examined consisted of survey responses from over 108 000 students a 25 random sample of the 2014 cohort dataset Within the group of students who participated in honors courses 6 609 students indicated their gender and 5 507 students indicated being in an ethnic racial group Inferential statistical procedures revealed the presence of similar percentages of male and female students had enrolled in honors courses Statistically significant differences were present however in student enrollment by ethnicity race The percentage of Hispanic students participating in honors was less than expected whereas the percentage of Black students participating was higher than expected Smaller class sizes and opportunities for greater engagement with faculty may benefit both Hispanic and Black students two student groups that have had less success in community colleges Implications and suggestions for further research were discussed
Keywords: honors; honors courses; honors students; honors programs; community college; community college survey of student engagement; CCSSE